Mispronounced Consonants Of Basic Listening And Speaking Students Of Universitas Klabat - Billy Melvin Sakul (Bandar Lampung University (UBL), 2013)
Oral proficiency has been one of the important goals in teaching English as a Foreign Languange (EFL) since it is important not only in communication, but also in other language skills such as reading and writing, which obviously overlay the path to student’s academic achievement. A study was conducted to examine mispronounced words by 34 EFL Freshmen FKIP students at the Klabat University who were taking Basic Listening and Speaking Subject. More specifically, this study aimed to find out the mispronounced voiced and voiceless consonants. To analyze the obtained data, a descriptive-quantitative method was used. The study is based on findings derived from a list of selected 397 English words taken from the students’ textbook. The words chosen appeared with their minimal pairs.Findings showed that the students could produce voiceless /p/, /k/, and /s/ sounds correctly but mispronounced the other five voiceless sounds: /t/, /k/, /f/, /θ/, /ʃ/, /ʧ/ and voiced consonant sounds: /b/, /d/, /g/, /v/, /ð/, /z/, /ʒ/, /ʤ/. The mispronunciation occurred elsewhere regardless the position of the consonants: initial, middle or final position.